The use of isotropic photorefraction for vision screening in infants. - Atkinson, J; Braddick, O (1983)
Isotropic photorefraction is a technique which makes possible the rapid, economic, large scale screening of infants and young children for refractive errors. The relative size of blur circles reflected from the fundus in 3 flash photographs with different camera settings allows the size and direction of refractive errors to be estimated. The method has been validated against retinoscopic measures on a large group of infants. Findings of a high incidence of astigmatism in the first year are confirmed. Detection of hypermetropia in early infancy by this screening procedure may allow preventive treatment for accommodative strabismus.